Електричні та магнетні властивості багатокомпонентних аморфних металевих композицій на основі заліза - Герцик, О.М.; Переверзєва, Т.Г.; Ковбуз, М.О.; Бойчишин, Л.М.; Носенко, В.К.; Борисюк, А.К. (Металлофизика и новейшие технологии, 2017)
Досліджено вплив елементного складу аморфного стопу, форми зразків, а також умов одержання (швидкість охолодження) за стандартною технологією на електромагнетні властивості стрічкових та об’ємних зразків стопів, виготовлених з однакової шихти. Исследовано влияние элементного состава аморфного сплава, формы образца, а также условий получения (скорость охлаждения) по стандартной технологии на электромагнитные свойства ленточных и объёмных образцов сплавов, изготовленных из одинаковой шихты. Influence of the elemental composition of amorphous metal alloy (AMA), the shape of its final product, and the fabrication conditions (cooling rate) according to standard technology on the electromagnetic characteristics of tape and bulk samples of alloys made from the same feedstock is investigated. A lower cooling rate in the process of obtaining bulk alloys (10³ K/s), compared to the tape samples (10⁶ K/s), increases structuring of bulk samples and causes higher divergence of surface elemental composition from the original feedstock. In the case of bulk samples, higher electrical resistance of cuts shows conservation of the amorphous phase inside the samples, compared to the surface. Due to the small size of nanocrystals formed during process of crystallization of the amorphous alloys, magnetostriction may be suppressed, and coercive force may be changed.